2014
DOI: 10.1007/s00384-014-2095-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendectomy for complicated appendicitis in high risk patients

Abstract: Laparoscopic appendectomy can be recommended for patients with complicated appendicitis even with higher risk categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
1
14
1
1
Order By: Relevance
“…Advanced age range was correlated with a longer evolution of the disease in several analyzes, mainly due to its atypical presentation, which leads to a late diagnosis possibly influencing the type of appendicitis at surgery, with an increase in complicated appendicitis [17][18][19][20] . In contrast to other studies, our work did not show statistical difference in the rate of complications when related to gender [20][21][22] .…”
Section: Society Of American Gastrointestinal and Endoscopiccontrasting
confidence: 99%
“…Advanced age range was correlated with a longer evolution of the disease in several analyzes, mainly due to its atypical presentation, which leads to a late diagnosis possibly influencing the type of appendicitis at surgery, with an increase in complicated appendicitis [17][18][19][20] . In contrast to other studies, our work did not show statistical difference in the rate of complications when related to gender [20][21][22] .…”
Section: Society Of American Gastrointestinal and Endoscopiccontrasting
confidence: 99%
“…In one study, it was reported that the risk of complications was in patients who were operated for AA increased from the age of 38.5 years, 17 and in another study complication risk was higher in patients aged 39 and older 18 . However, there was no significant difference in postoperative complications with regard to age 19 . In another study of 372 patients operated with the diagnosis of acute appendicitis, it was reported that patient age, leucocyte and CRP level, duration of the surgical operation, presence of comorbid disease, ASA score, and length of hospital stay were risk factors for the development of infectious complications in patients with complicated appendicitis.…”
Section: Discussionmentioning
confidence: 92%
“…In the retrospective cohort study by Werkgartner et al investigating the benefits of LA in patients with high peri-and postoperative risk factors (ASA 3 and 4), LA was associated with slightly longer operative times and shorter hospital stay. Overall complications, graded according to the Clavien-Dindo classification, were slightly more frequent in patients after LA, whereas severe complications occurred more frequently in patients after OA [153]. For high-risk patients, LA has proven to be safe and feasible and was also associated with decreased rates of mortality, postoperative morbidity, and shorter hospitalization.…”
Section: Q44: Does Laparoscopic Single-incision Surgery Confer Any mentioning
confidence: 99%